THE SIGNIFICANCE OF TEACHING FOREIGN LANGUAGES ON COMMUNICATION APPROACH - Giyasova Dilafruz Xamzayevna; Shavkatova Hulkar Xasan qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article examines the significance of teaching foreign languages through the communicative approach in modern education. In contemporary language pedagogy, the communicative approach is considered one of the most effective and widely accepted methods because it emphasizes the practical use of language in real-life situations rather than the memorization of isolated grammar rules and vocabulary items.  The  problem  addressed  in  this  study  lies  in  the  need  to  develop  learners’ communicative competence, fluency, and confidence in using a foreign language for meaningful  interaction  in  academic,  social,  and  professional  contexts.  The methodology of the research is based on a qualitative theoretical approach, including descriptive  analysis,  comparative  interpretation,  and  review  of  methodological  and pedagogical literature related to communicative language teaching. The study analyzes the  theoretical  foundations  of  the  communicative  approach,  its  main  principles, classroom  applications,  and its  role  in developing  listening, speaking, reading, and writing skills in an integrated way. The main findings of the research show that the communicative  approach  significantly  improves  learners’  ability  to  use  a  foreign language effectively in authentic situations. It encourages active participation, learner-centered  instruction,  interaction,  collaboration,  and  real-life  communication.  The approach also supports the development of communicative competence, sociolinguistic awareness, strategic language use, and learner autonomy. In addition, it creates a more motivating  and  engaging  classroom  environment  than  traditional  teacher-centered methods.